2015
DOI: 10.1111/ajt.13360
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia and Liver Ischemia Reperfusion Injury: A Role for the Advanced Glycation Endproduct and Its Receptor Pathway

Abstract: Although pretransplant diabetes is a risk factor for mortality post-liver transplant, the underlying mechanism has not been fully defined. In a murine liver partial warm ischemia model, we addressed the question of how diabetes/hyperglycemia impacted tissue inflammatory injuries against ischemia reperfusion (IR), focusing on the advanced glycation endproduct (AGE) and its receptor (RAGE) pathway. Our results showed that hepatocellular injury was exacerbated in streptozotocin-induced diabetic mice against IR, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 35 publications
1
30
0
1
Order By: Relevance
“…The roles of S1PR3 in IRI may be organ specific, which is perhaps related to cell‐specific expression of S1PR3 . Previous studies have shown that DM increases susceptibility to IRI and that inflammation is an important factor in diabetes . In this study, we found that the S1P/S1PR3 pathway was activated in the KCs of hyperglycemic mice and that CAY10444 could suppress hepatocellular injury and inflammation after IR in STZ‐treated mice but not in control mice.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The roles of S1PR3 in IRI may be organ specific, which is perhaps related to cell‐specific expression of S1PR3 . Previous studies have shown that DM increases susceptibility to IRI and that inflammation is an important factor in diabetes . In this study, we found that the S1P/S1PR3 pathway was activated in the KCs of hyperglycemic mice and that CAY10444 could suppress hepatocellular injury and inflammation after IR in STZ‐treated mice but not in control mice.…”
Section: Discussionmentioning
confidence: 55%
“…Overwhelming epidemiological and clinical data have demonstrated that patients with DM are more sensitive to IRI . Diabetes and its associated hyperglycemia are involved in a variety of ischemic tissue injuries, including in the lungs, brain, kidney, and liver . The numerous functions of S1P include the regulation of cell death, proliferation, motility, differentiation, and inflammation .…”
Section: Discussionmentioning
confidence: 99%
“…) and ischaemia/reperfusion injury (Yue et al . ). In the present study, the increase in AGE deposition in the liver of the diabetic animals is the first indication of the participation of AGE‐RAGE pathway in diabetic‐induced liver damage.…”
Section: Discussionmentioning
confidence: 97%
“…Two functional mechanisms downstream of RAGE activation were demonstrated important for the disease pathogenesis, Egr-1-mediated MIP2 expression, and Egr-1-independent TNF-a production and apoptosis. We have found in a liver partial ischemia model that RAGE antagonist peptides or shRNA protected livers from early stage IRI only in hyperglycemic, but not normal, hosts 20 . Although functional roles of CD24/Siglec in liver IRI remain to be determined, CD24 deficient mice suffered significantly higher levels of tissue damage in an acetaminophen (AAP)-induced liver injury model by increasing inflammatory cytokine/chemokine production, indicating its negative regulatory roles in liver innate immune responses.…”
Section: Innate Immune Activationmentioning
confidence: 90%